2004
DOI: 10.1523/jneurosci.1315-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Controllability Modulates the Neural Response to Pain

Abstract: The response to painful stimulation depends not only on peripheral nociceptive input but also on the cognitive and affective context in which pain occurs. One contextual variable that affects the neural and behavioral response to nociceptive stimulation is the degree to which pain is perceived to be controllable. Previous studies indicate that perceived controllability affects pain tolerance, learning and motivation, and the ability to cope with intractable pain, suggesting that it has profound effects on neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
148
4
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(168 citation statements)
references
References 29 publications
13
148
4
3
Order By: Relevance
“…The defining characteristic of this process is an exponential growth up to the outcome. We found ample evidence for this process throughout the cortical pain matrix, a result consistent with previous studies of pain anticipation (6,7,(27)(28)(29)(30)(31). Unlike previous studies, we are now able to identify neurobiological substrates associated specifically with a second component of anticipation: dread.…”
supporting
confidence: 88%
“…The defining characteristic of this process is an exponential growth up to the outcome. We found ample evidence for this process throughout the cortical pain matrix, a result consistent with previous studies of pain anticipation (6,7,(27)(28)(29)(30)(31). Unlike previous studies, we are now able to identify neurobiological substrates associated specifically with a second component of anticipation: dread.…”
supporting
confidence: 88%
“…In contrast, other effects, such as acceleration of visual reaction times (Longo and Haggard, 2009) and proprioceptive integration (Tsakiris et al, 2006), appeared to be related to agency. It is well established that perceived control reduces both the subjective experience of (Weisenberg et al, 1985) and neural responses to (Salomons et al, 2004) pain, via modulation of anterolateral prefrontal regions involved in pain appraisal (Wiech et al, 2006). It is therefore possible that our effects are mediated by an increased sense of bodily control when viewing the hand.…”
Section: Discussionmentioning
confidence: 87%
“…Studies using the learned helplessness paradigm have taught us that an organism is advantaged when having control over aversive events compared with having no control (Abrahamson et al, 1978;Seligman, 1972). Evidence is accumulating that the (perceived) ability to control pain by behavioural responses results in less pain (e.g., Wiech et al, 2006) and decreased activation in neural areas usually linked with pain processing (anterior cingulate, insular, and secondary somatosensory cortices) (e.g., Salomons et al, 2004). Furthermore, several studies have identified the neurobiological basis for processes that are central in pain control such as cognitive reappraisal (Wiech et al, 2006) and motor preparation (Morrison et al, 2007).…”
Section: Effects Of "Real-life" Pain Goalsmentioning
confidence: 99%